Factors which Have an Influence on Labial Inclination of Lower Incisors During Expansion Therapy with Fixed Appliance - Z. Hanuliaková; I. Marek (Czech Dental Chamber, 2015)
Introduction and objective: The expansion therapy is one of the methods for treatment of orthodontic anomalies. Proclination of lower incisors labially is often used to treat mild or medium serious crowding of Angle class I, to treat malocclusion of Angle Class II, division 1 and 2 type and also for treatment skeletal Class III by decompensation of position of lower incisors before orthognatic surgery. Labial inclination of lower incisors causes lengthening of lower dental arch. Excessive anterior inclination of lower incisors is generally considered as a highly risk movement potentially causing instability of orthodontic treatment outcomes and developing gingival recessions.Our aim is to point out the factors influencing anterior inclination of lower incisors towards the line A-Po and ML. Material and methods: This retrospective study includes 159 patients with nonextraction therapy of lower dental arch during fixed orthodontic appliance treatment. From the patient's documentation there was located the use of the "antispee" metal arches, the use of the class II elastics and the use of stripping of lower incisors during treatment. The position and inclination of lower incisors towards A-Po and ML line was evaluated from the cephalometric X-rays. The discrepancy and the depth of the curve of Spee were evaluated from the model casts. Results and conclusion: There was no significant dependence between observed factors and the rate of labial inclination of lower incisors towards A-Po line. However with regard to ML line the lower incisors were significantly protruded by using "antispee" metal arches for deep bite correction and also when the level of crowding increased. So we can say that observed factors influence just the labial inclination of lower incisors towards ML line with no relation towards A-Po line.